Investigation of serum surfactant protein a and d levels in children exposed to cigarette smoke - Huseyin, Gumus; Halil, Kazanasmaz; Zeyrek, Cemalettin Dost (Indian Journal of Child Health, 2018)
Background: Depending on the degree of exposure to cigarette smoke, various health problems can emerge in children. It is needed to have biochemical data of passive smoking to define the risks and to count the benefits of anti-smoking responses. Objective: The objective of the study was to evaluate the effect of smoke exposure on the surfactant protein (SP) A and D by measuring the cotinine level in the lungs of the children who are exposed to passive cigarette smoke. Methods: This case–control study was conducted between December 2012 and September 2013. ?n this study, total 79 children were included who were admitted to the general pediatric outpatient clinic of a medical university. Out of them, 51 children were exposed to cigarette smoke and 28 children were not exposed to cigarette smoke. In a survey was applied to evaluate the smoke exposure, and urinary cotinine levels were measured. Cotinine level was measured by chemiluminescence method (children’s urines are used), and serum SP-D and SP-A levels were measured by ELISA method (peripheral venous blood is used). Results: The average urinary cotinine level of the children who were exposed to smoking was 622.27±600.66 ng/ml and 4.25±7.50 ng/ml of the children who were not exposed. The mean serum SP-A level was high (2.64±0.78 U/L) in children exposed to smoking than that in non-exposed children (2.2±0.76 U/L) and this difference was statistically significant (p